Constructing Spiritual Meaning in Kawniyyah Verses: A Sufistic Hermeneutical Study of Haqā’iqu at-Tafsīr - T. Mairizal (ISTIFHAM, 2025)
The interpretation of Kawniyyah verses in Haqā’iqu at-Tafsīr by Abu ‘Abdirrahmān as-Sulamī highlights the dialogue between modern scientific approaches and the Sufistic-Isyārī style. This study employs a qualitative library research method, with content analysis and a thematic approach, to examine verses concerning the sun, moon, earth, mountains, rivers, and stars. Primary data were obtained from the text of Haqā’iqu at-Tafsīr, while secondary data came from literature on Isyārī tafsir and scientific interpretation of Kawniyyah verses. The findings show that as-Sulamī interprets cosmic phenomena not only as physical realities but also as spiritual symbols: the sun as al-ma'rīfah illuminating bodily faculties, the moon as al-uns purifying intentions, mountains as saints stabilising the soul, rivers as organs of remembrance, and stars as lights guiding the heart. This interpretation is presented in the form of parables, thus not negating the zhāhir meaning nor falling into the blameworthy tafsir bi al-ra’y. The study identifies a research gap: previous works tend to separate Isyārī from scientific tafsir. In contrast, this research offers a dialogical reading that places Sufi cosmology alongside modern scientific discourse on Kawniyyah verses. The novelty of this study lies in its systematic mapping of Kawniyyah verse interpretations in Haqā’iqu at-Tafsīr and in its demonstration of the potential for developing contemporary tafsir studies that integrate revelation, spirituality, and scientific knowledge